POLEMIK PARA ULAMA MENGENAI KEKALNYA SURGA YANG DITEMPATI ADAM DAN HAWA DALAM AL QUR’AN - Hermansyah (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2024)
The discussion regarding the location of the paradise where Prophet Adam and Eve resided has long been a subject of debate among scholars. This article analyzes the majority opinion of scholars, which asserts that the paradise in question is the Eternal Paradise in the hereafter, as well as the minority view that considers it to be located on earth. This study employs an analytical approach to the evidence found in the Qur'an, hadith, and the perspectives of classical and contemporary scholars. The findings indicate that the majority opinion is stronger, based on clear and authentic arguments.